Análise preliminar dos fatores que contribuem para a incidência de retratamentos endodônticos de dentes tratados nos cursos de graduação em odontologia e especialização em endodontia de uma instituição de ensino do sul do Brasil : estudo retrospectivo - Togni, Lidiane (2022)
The present retrospective study analyzed the factors that contribute to the incidence of endodontic retreatments of teeth treated in the Dental School and Specialization Course in Endodontics at the Pontifical Catholic University of Rio Grande do Sul (PUCRS) from March 2015 to December 2019. Data collection was performed based on the medical records of patients treated at the PUCRS Dental Care Unit. Sociodemographic and general health data from the patients were collected. In addition to specific data on endodontic treatment and retreatment: tooth number, beginning and ending of the treatment, discipline in which the treatment was performed, complications during and after the end of treatment, type of temporary sealing between appointments and at the end of the treatment, number of sessions until the end of treatment, endodontic sealer, referral for restorative treatment, identification of urgent care during the referral period, completion of the final restorative treatment (type, date and discipline), reasons for the indication of endodontic retreatment, indication of extraction. Preliminary results were presented using descriptive statistics. A total of 401 endodontically retreated teeth were identified in the period, with 35 endodontic retreatments of endodontically treated teeth at PUCRS, reaching an incidence of 8.7%. Of the 33 patients (35 teeth) included in the sample, 21 (64%) were female and 12 (36%) were male with a mean age of 57.1 years (SD = 13.0). 87.9% (n = 31) of patients reported having some systemic condition. Anterior teeth and premolars were more frequently treated (n = 30, 85.8%). The main factors for endodontic retreatment indication were loss of temporary sealing in 11 teeth (31.4%), 5 teeth (14.3%) were diagnosed with apical periodontitis and 3 teeth (8.6%) had the retreatment recommended because of technical reasons. Of the 35 teeth indicated for retreatment, 5 teeth (14.3%) had received the final restoration after the primary treatment. After retreatment, 23 (74.2%) received the final restoration. Of the 31 endodontic retreatments performed, 6 teeth (19.3%) were extracted, of which 4 (12.9%) remained with the temporary restoration since the conclusion of the retreatment. Preliminary results suggest that the incidence of endodontic retreatments seem to be associated, much more, with issues of patient flow that led to failure than, necessarily, to the failure of the primary endodontic treatment itself.